Manajemen peningkatan produktivitas remaja Desa semen di bidang ekonomi melalui pelatihan Fotografi dan Videografi - Nahdya Richana Putri; Siti Kalimah, M.Sy (LP3M IAIFA Kediri, 2021)
Productivity is a form of activity carried out to produce a product or service. Productivity is the ability of each person, system or company to produce something desired by utilizing resources effectively and efficiently. Adolescence is a period of expression and self-discovery. Many creative and innovative ideas emerge from teenagers. But not a few teenagers who spend their time on activities that are not useful. May even harm yourself and other. To avoid these things. Teenagers must realize the importance of being productive teenagers, namely teenagers who maximize their time to do useful activities. The purpose of service is to increase productivity, youth in Semen Village, Pagu Subdistrict. Job opportunities in the field of photography are very large because the multimedia and social media needs are increasingly in demand. In this digital era, there are many fields that require photographers, such as journalism, fashion, food product, models, not infrequently even celebgram, bloggers, youtubers currently have their own personal photographers to support their work.